(untitled) (Teacher’s World: Journal of Education and Research, 2024)
The qualitative research study explored Bangladeshi secondary science teacher’s experiences working in a professional learning community (PLC) in terms of enhancing professional knowledge in learning pedagogical content knowledge (PCK). The research questions that guided this study are: (1) What are the learning experiences of the secondary science teachers regarding their involvement in a Professional Learning Community (PLC) as a means of professional learning for enhancing their Pedagogical Content Knowledge (PCK)? (2) How do Secondary Science teachers apply their learning from Professional Learning Communities (PLC) to their teaching plans and practices through the Content Representation (CoRe) framework? (3) How do secondary science teachers use the knowledge gained from participation in a professional learning community (PLC) to design and implement effective teaching strategies in their classrooms? The study is based on a constructivist approach to learning, which views knowledge construction as a socially mediated process. Therefore, teachers’ experiences were collected as qualitative data through analyzing teachers’ lesson plans and self-reflective journals. As a result, the findings showed teacher’s enhanced professional knowledge working in a PLC in sizing up the topic, identifying the importance of the topic, exploring self-content knowledge relevant to the topic, knowing what learners might think, identifying contextual factors choosing the topic and examples, selecting more appropriate teaching-learning and assessment strategies. The findings of this study are expected to provide insights into how PLCs can be utilized to enhance secondary science teacher’s PCK knowledge. This study is significant as it contributes to the literature on professional development for science teachers and offers practical recommendations for improving science teacher’s professional knowledge in learning PCK. Teacher’s World: Journal of Education and Research, 49 (1), 155-174